Energy needs of athletes - Burke, L. M. (Canadian Journal of Applied Physiology, 2001)
Each athlete has unique energy requirements, which underpin their ability to meet total nutritional goals. For everyday dietary planning and evaluation, energy requirements can be predicted via estimations of RMR and activity levels. Research methods such as indirect calorimetry and DLW allow energy requirements to be measured, and may be useful to confirm situations in which an athlete has a true energy balance anomaly. There is some evidence that individual athletes may have reduced energy requirements, although this occurs less frequently than is reported. Most self-reports of food intake substantially under-estimate energy intake, due to under-reporting or under-eating during the period of record keeping. Many athletes are over-focused on reducing body mass and body fat below levels that are consistent with long-term health and performance. Restrained eating can cause significant detrimental outcomes to body function. Leptin may be involved in modulating or mediating some of these changes. Athletes should use their energy budget to choose foods that provide macronutrient and micronutrient needs for optimal health and performance. Practical advice may help athletes to achieve energy intake challenges.